PERANAN PASAR MODAL DALAM PEREKONOMIAN NEGARA INDONESIA - Citra Puspa Permata; Muhammad Abdul Ghoni (LPPM Universitas Bina Insan, 2019)
The role of the capital market as a source of corporate approval has implications for the state not only as an alternative but has become the main source. Funds are offered on the capital market through several corporate actions such as the initial listing of Shares (initial public offering), new rights listing (rights issue), Bond, Derivative, and Reksadana agreements that are accessible every day to increase permits needed by the company from bank loans. In particular, the growth trend is increasing which does not directly affect the interest rates of bank loans. The number of prime listed companies, rights issue, bond and also issued sources listed in the capital market collected. However, there are fluctuations, one of which is issued at home and abroad, in each year, but this does not sort the company to still get results. in the capital market.